ANALISIS FAKTOR RISKO KEJADIAN STUNTING PADA ANAK BALITA USIA 6-59 BULAN DI DAERAH PESISIR WILAYAH KERJA PUSKESMAS BONE ROMBO - I Putu Sudayasa; Wa Ode Salma; Irma Irma; Nirmala Sari Putri (NHM PRESS, 2022)
Linear inappropriate growth or stunted growth, is considered a major public health problem among children worldwide. The purpose of this study was to analyze the risk factors for stunting in children aged 6-59 months in the coastal area of ​​the Bone Rombo Health Center. This research method is an analytic observational research, which uses a case control study design. The number of research samples were 96 children under five. The sampling technique uses the Proportional Random Sampling Technique method. The bivariate data analysis technique uses the Odds Ratio test and the results of the study using the Odds ratio test show that education with a value of (OR = 2.783), income (OR = 3.095), the conclusion of the study is low maternal education and low family income are risk factors for incident stunting in children aged 6-59 months in the coastal area of ​​the Bone Rombo Community Health Center, North Buton Regency.